Silent no more - Parsley, Rod. (Columbus, OH : Breakthrough: a media ministry of World Harvest Church, 2005)
"How can we afford to be silent while America's moral currency is plumetting to a historic low? How can we distort the message that the Kingdom of God is depicted as a celebration of God's gloriuos human diversity? How can we stand by and watch the war on poverty become a war on the poor...where welfare has become a trap, victimizing the people it was intended to help?" - - Container.
Disc 1: Life - - Disc 2: Race - - Disc 3: Poverty - - Disc 4: Islam - - Disc 5 Silent No More
Keywords: Christianity and culture -- United States; Christianity and politics -- United States; Church and state -- United States; United States -- Church history -- 21st century